The Influence of Spanish Lexicon on Limonese Creole : negative Implications - Pizarro Chacón, Ginneth (2014)
After working in the construction of the railroad that communicates Limón with San José, many Afro-Caribbean people who had arrived during the 1870’s, especially from Jamaica, stayed and established themselves in Limón. In the 20th century, some Costa Rican Spanish speakers started to migrate to Limón; as a result, their Spanish language influenced Limonese Creole and made speakers start substituting some English lexicon, root morphemes, and word order for the Spanish one. As time has passed, more Costa Rican Spanish elements have been incorporated and mixed into the English Creole. In addition, many of the inhabitants of Limón who spoke Limonese Creole moved to San José and adopted Spanish. Depending on the event or situation, Limonese use either Costa Rican Spanish, Limonese Creole, or code-switch between both of them. The chief purpose of this research is to investigate and analyze the influence of Costa Rican Spanish lexicon on Limonese Creole and how this English variety has been affected by its Costa Rican Spanish influence.